REALIZATION OF COMPETENCE APPROACH IN PREPARATION OF FUTURE PHYSICS TEACHER: REALITY AND PROSPECTS - Volodymyr P. Serhiienko (Інформаційні технології і засоби навчання, 2010)
In the article is written about the theoretical bases of formation of physical knowledge, acquirement of the persuasions and competentions by future teachers.